1990
DOI: 10.1346/ccmn.1990.0380202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrazine on the Vibrational Modes of Kaolinite

Abstract: Abstract--Raman and Fourier-transform-infrared (FTIR) spectroscopic methods and X-ray powder diffraction (XRD) techniques have been used to study the influence of hydrazine on the vibrational modes of kaolinite. Strong vibrational perturbations of the OH-stretching and -deformation bands were observed in the Raman and FTIR spectra on intercalation. The intensities of the Raman-and IR-active OHstretching bands decreased significantly upon intercalation; the intensities of the Raman bands were reduced to a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 33 publications
12
59
0
Order By: Relevance
“…Johnston et al also reported two bands at 3368 and 3363 cm -1 for the 10.3Å phase of hydrazine-intercalated kaolinite and that these two bands coalesced into a single band at 3363 cm -1 for the 9.5Å phase (6,10). In this work we find two bands at 3356 and 3362 cm -1 , which are present for both the 10.3 and 9.5Å phases.…”
Section: Drift Spectroscopy Of the Amine-stretching Regionsupporting
confidence: 74%
“…Johnston et al also reported two bands at 3368 and 3363 cm -1 for the 10.3Å phase of hydrazine-intercalated kaolinite and that these two bands coalesced into a single band at 3363 cm -1 for the 9.5Å phase (6,10). In this work we find two bands at 3356 and 3362 cm -1 , which are present for both the 10.3 and 9.5Å phases.…”
Section: Drift Spectroscopy Of the Amine-stretching Regionsupporting
confidence: 74%
“…These authors also demonstrated that a variable fraction of the starting sample does not react with hydrazine, whereas some kaolinite specimens react slowly and lead to complexes with a basal spacing of 9.5-9.6 A. A similar spacing was observed by Johnston and Stone (1990) during hydrazine loss at decreasing pressure, and this was interpreted as relating to the structural rearrangement caused by the loss of a portion of the intercalated hydrazine. Frost et aL (1998) and Kloprogge et al (1999) showed XRD patterns of K-H complexes with broad basal reflections, consisting of three overlapped peaks with d values of 10.28, -9.50, and -8.80 A.…”
Section: Introductionmentioning
confidence: 55%
“…This intermediate intercalation complex also showed a d value slightly lower than the 9.6 ,~ measured in the K-H complex. This "contracted" complex was observed by Johnston and Stone (1990) during hydrazine loss at decreasing pressure and interpreted, from IR spectra, as owing to the keying of the hydrazine molecules into the ditrigonal cavities of the tetrahedral sheet. Recently, Frost et al (1998) and Kloprogge et al (1999) proposed that intercalation takes place in steps.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations